(untitled) (Research, Society and Development, 2021)
Health workers are usually subjected to precarious working conditions, stress and occupational hazards. In addition, there was the introduction of new requirements of public management, through Social Organization (OS), accompanied by the implementation of quality certification standards, with accreditation being more frequent. This study aimed to evaluate the implications of OS management and accreditation on the health of workers at a unit of the Unified Health System (SUS), under their and managers’ perception. A qualitative approach was used, supported by thematic content analysis. The study was carried out in a mixed health unit of the municipal SUS network, administered by OS and certified by accreditation. Focus group and individual interview techniques were used, by intentional sampling. The results showed agreement between managers and workers regarding the benefits of accreditation, however, they reveal counterpoints regarding the implications for workers’ health. From this perspective, workers report worsening of their health and well-being, overload of assignments and high demands for goals/indicators, and also excessive documentary records, aspects that are not recognized by managers. Furthermore, workers state that OS management leads to: insecurity, fear of job termination, low perspective of appreciation, professional dissatisfaction and illness. Therefore, it is imperative to minimize the harmful effects on workers’ health, by promoting democratic negotiation spaces, essential for equitable, co-participatory and effective decision-making in the application of practical measures to promote and protect workers’ health, concomitant with the process of accreditation.